Towards An Affective Robot Companion for Audiology Rehabilitation: How Does Pepper Feel Today? - Uluer, Pinar; Kose, Hatice; Bulent Koray Oz; Aydinalev, Turgut Can; Barkana, Duygun Erol (IEEE, 2020)
The motivation of this work is to develop an affective robot companion for audiology rehabilitation and to test the system with the deaf or hard of hearing children. Two robot modules are developed which are the multimodal "stress/emotion/motivation" recognition module for the robot to "understand" how the children feel, and behaviour and feedback module of the robot to show the children how the robot "feels". In this study we only focus on the behaviour and feedback module of the robot. The selected affective/affirmative behaviours are tested by means of tablet games and employed on the robot during an audiology test, as a feedback mechanism. Facial data are used together with the surveys to evaluate the children’s perception of the robot and the behaviour set.